Performance of field-aged polymeric spray lining for water pipe rehabilitation. (October 2021) - Azoor, Rukshan; Shannon, Benjamin; Fu, Guoyang; Deo, Ravin; Kodikara, Jayantha
Highlights: We tested field-aged liners and lined-pipe composites to assess their performance. Spray liners reduce leakage and can span small holes and gaps in deteriorated pipes. Water leakage between liner and cement mortar liner interface needs consideration. End, joint and service connection sealing are critical for spray liner performance. Abstract: Polymeric spray lining is a trenchless pipe rehabilitation technique which is rapidly gaining momentum, due to the increasing costs of open trenching or lift-and-relay replacement. An accurate assessment of the effectiveness of polymeric spray-lining products is best conducted on specimens from field spray-liner installations, since field application of the polymer spray varies in application quality and installation length in comparison with laboratory-controlled application. Furthermore, experimental testing on spray-lined pipes needs to be as close as possible to actual field conditions. This paper presents results from a comprehensive testing program intended to evaluate the performance of actual in-service, spray-lined pipes extracted from the field. Material property tests on the liner material and full-scale tests on the lined pipe composites were conducted. Results indicated that despite degradation of the material in comparison to the initial conditions, the lined pipes were able to withstand operational pressures with circular through-wall holes in the host pipe of up to 50 mm diameter. Circumferential cracks in the host pipe were also successfully spanned under water pressure and pipe bending. However, water leakage, which can occur at the interface of the cement mortar liner and the polymeric liner was identified as a major issue that could compromise lined pipe systems. Recommendations for the mitigation of this issue are provided on the basis of the experimental observations.